Muy bien, Fergus! - Shannon, David, 1959- (New York : Scholastic Inc., 2006)
A colorful and beautifully illustrated picture book about a dog named Fergus.
"Scholastic en español"--Cover.
Keywords: Dogs -- Juvenile fiction; Perros -- Novela juvenil